Diminished antimicrobial drug use in dogs with allergic dermatitis treated with oclacitinib - Mwacalimba, Kennedy; Hillier, Andrew; Rosenbaum, Michele; Brennan, Christopher; Amodie, Deborah (Frontiers in Veterinary Science, 2023)
Dogs with allergic dermatitis often suffer concurrent skin and ear infections. The objective of this study was to retrospectively quantify the number of systemic and topical antimicrobial transactions in dogs with allergic dermatitis, following administration of oclacitinib or a glucocorticoid compared to dogs that did not receive a pruritus therapy, when there is an initial diagnosis of pyoderma. A secondary objective was to demonstrate that dogs on oclacitinib use fewer antimicrobials and concomitant therapies, over time.This was a retrospective case control study using a large, centralized database to identify canine patients receiving a pruritus therapy along with a concurrent diagnosis of pyoderma. For the second objective, 58 client-owned dogs diagnosed with allergic dermatitis were enrolled in a prospective quality of life and treatment satisfaction (QoL&TS) study that also evaluated concomitant therapy use over time.In Part A, data were anonymous transaction records from 1,134 hospitals across the United States, representing pyoderma visits between December 2018 and December 2019. Odds ratios comparing the relative odds of having additional antimicrobial agent transactions were calculated, given an initial pruritus therapy compared to dogs that did not receive a pruritus therapy. Parametric bootstrapping was used to calculate goodness-of-fit statistics. In part B, dogs entered the study on Day 0 and returned for examination on Days 14, 21, 30 and 60. Owner determination of QoL&TS was performed on Days 0, 1, 3, 14, 21,30 and 60. On Days 0, 14, 21 and 60, a veterinarian assessed concomitant therapies and dermatitis-severity scoring. Percent reduction in therapies was then calculated. Dogs that received oclacitinib (n=5,132) or a glucocorticoid (n=7,024) had reduced odds (OR: 0.8091; P=0.0002 and OR: 0.7095; P<0.0001, respectively) of having a follow up antimicrobial drug transaction after the initial antimicrobial therapy compared to dogs with no pruritus therapy at the initial visit (n=12,997). For objective 2, 83% fewer concomitant dermatologic therapies were provided after 60 days on oclacitinib. Importantly, there was 100% reduction in systemic antimicrobials associated with dermatologic care and an 88% reduction of topical antimicrobial agents as well. This suggests that use of oclacitinib to treat allergic dermatitis is associated with less antibacterial use.